2006
DOI: 10.1111/j.1464-5491.2006.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adipocytokines in non‐diabetic and Type 1 diabetic children: relationship to insulin therapy, glycaemic control and pubertal development

Abstract: Circulating concentrations of adipocytokines are abnormal in Type 1 diabetic children, although the direction of change differs by cytokine. Pubertal development, in addition to insulin treatment and glycaemic control, also influences the concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
4
31
1
2
Order By: Relevance
“…No significant difference in adiponectin concentrations regarding gender was seen. This observation is confirmed by the paediatric studies where gender differences were not seen either (26,27). In contrast, the published studies in adults report on higher levels of adiponectin in women (12,(23)(24)(25).…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…No significant difference in adiponectin concentrations regarding gender was seen. This observation is confirmed by the paediatric studies where gender differences were not seen either (26,27). In contrast, the published studies in adults report on higher levels of adiponectin in women (12,(23)(24)(25).…”
Section: Discussioncontrasting
confidence: 47%
“…In contrast to adults, studies in children and adolescents with type 1 diabetes show controversial results (26,27). Celi et al reported elevated levels of adiponectin in pre-pubertal children with type 1 diabetes (27). The study by Morales et al revealed that adiponectin levels in children and adolescents with type 1 diabetes did not differ from those in healthy subjects (26).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations